High task interdependence: job rotation and other approaches for overcoming ingroup favoritism. Issue 4 (2nd May 2017) - Wagner, Jürgen P.; Grigg, Nigel; Mann, Robin; Mohammad, Musli
Abstract : Purpose: The purpose of this paper is to investigate how the basic problem of ingroup favoritism in a setting of high task interdependence is addressed through an intervention strategy combining different approaches. Design/methodology/approach: This paper reports on evidence from extensive field-based case research. It focuses on the holistic description of a single high-performance logistics setting and discusses the distinct but interrelated managerial approaches against the backdrop of behavioral theory. Findings: Most notably, the authors examine how culturally specific factors such as people's social ingroup-outgroup categorization is reduced through a continual rotation of jobs. Work relationships are purposefully depersonalized and consequently socially reframed through reference to the corporate philosophy. Likewise, behaviors, roles and responsibilities are redefined based on a purposeful reinterpretation of the corporate philosophy. The authors evaluate these desired behaviors against the background of the perceptions of work group members and describe how these guide actual behaviors. Practical implications: The insights of this study exemplify how adverse behavioral effects that may occur in some socio-cultural contexts may be avoided through the appropriate design of operations. Originality/value: This study employs a holistic approach to provide valuable insights into both practitioners and academics in the field of OM to counteract detrimental behavioral effects in real-world operations.